Factors Influencing Malnutrition in Children at the out Patient Clinic of the Pediatric Nutrition Sub Division, Dr. Pirngadi Hospital Medan in 1985 - 1989 - Rosmaida S. Sitanggang; Tjut Dharmawati; Robroy Nasution; Endang D. Hamid; Sjarikat Tarigan (Indonesian Pediatric Society, 1993)
A retrospective study on the incidence of malnutrition and the influencing factors had been carried out on 1081 children attending the outpatient clinic of the Pediatric Nutrition, Dr. Pirngadi Hospital Medan during 1985-1989. Mild and moderate malnutrition were found in 69.96% of the children, severe malnutrition in 33. 77% while well nourished children were found in only 0.27% of cases. The highest incidence of malnutrition was in 12-24 months age group (43. 76%) (p<0.05). About half (49.08%) of cases were breastfed, and in 85.66% of them breast feeding were given until 6 months old. Most of the malnourished children were given very diluted milk (63.4%), while low protein supplementary feeding was given to 62.89% of children, and both types of food mentioned above were given to 52.52% of cases. The most prevalent accompanying diseases in malnourished children were gastroenteritis (58.25%), followed by respiratory tract infection (52.59%). The majority of father's occupation was seasonal workers (60.12%). Factors associated with malnourished children in this study were early weaning, low protein supplementary feeding and accompanying diseases especially diarrhea.